2017
DOI: 10.3390/nu9070767
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Prebiotic Effect of Lactulose in a Computer-Controlled In Vitro Model of the Human Large Intestine

Abstract: Lactulose, a disaccharide of galactose and fructose, used as a laxative or ammonia-lowering drug and as a functional food ingredient, enhances growth of Bifidobacterium and Lactobacillus at clinically relevant dosages. The prebiotic effect of subclinical dosages of Lactulose, however, remains to be elucidated. This study analyses changes in the microbiota and their metabolites after a 5 days Lactulose treatment using the TIM-2 system, a computer-controlled model of the proximal large intestine representing a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 27 publications
1
38
0
2
Order By: Relevance
“…At a low dosage (2-3 g), they observed an increase in Bifidobacteria, but not in Lactobacilli, and a low production of SCFAs, while the administration of the maximal experimental dose (5 g/day) determined the correct balance among the microbial population (Bifidobacteria, Lactobacilli and Anaerostipes) and SCFAs production. By further increasing the quantities (10 g/day), the authors observed a significant reduction in the production of butyrate and an increase in acetate, probably due to the growth of the bifidobacterium population, which usually produces acetate from its metabolism [59].…”
Section: Lactulosementioning
confidence: 98%
See 1 more Smart Citation
“…At a low dosage (2-3 g), they observed an increase in Bifidobacteria, but not in Lactobacilli, and a low production of SCFAs, while the administration of the maximal experimental dose (5 g/day) determined the correct balance among the microbial population (Bifidobacteria, Lactobacilli and Anaerostipes) and SCFAs production. By further increasing the quantities (10 g/day), the authors observed a significant reduction in the production of butyrate and an increase in acetate, probably due to the growth of the bifidobacterium population, which usually produces acetate from its metabolism [59].…”
Section: Lactulosementioning
confidence: 98%
“…At a low dosage (2-3 g/day), ↑ Bifidobacterium count [53,59], but not Lactobacilli, and determines a low production of SCFAs; 5 g/day determines the correct balance among the microbial population (Bifidobacteria, Lactobacilli and Anaerostipes) and SCFAs production, while 10 g/day ↓ butyrate production and ↑ acetate [59].…”
Section: Lactulosementioning
confidence: 99%
“…Former studies using a computer-controlled in vitro model of the human proximal colon revealed a dosedependent increase in total short-chain fatty acid (SCFA) concentrations upon low-dose lactulose supplementation of up to 5 g/day, mainly attributed to increased acetate, butyrate and lactate production [17,18]. Butyrate production, however, was inhibited when higher lactulose amounts (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Daily ingested by humans playing significant roles as health-promoting probiotics which is the most important point, to improve general health and protect from different kinds of illness [3][4][5][6]. Also used as production of food and feed throughout the world [7][8][9][10][11] because widely used in the food industry for the production and the preservation of fermented products such as wholegrain sourdough bread or sourdough fermentation [12,13].…”
Section: Introductionmentioning
confidence: 99%